Autonomous Electrical System Monitoring and Control Strategies to Avoid Oversized Storage Capacity. Issue 1 (July 2020) - Hong, T T Vu; Delinchant, Benoit; Ferrari, Jérôme; Nguyen, Quang D
Abstract: A significant solution to achieve energy efficiencies and stability of the electrical network is upgrading auto-consumption in a single PV system. In this paper, we presented a methodology to implement low-cost sensors and actuators to have better monitoring and control for a feasibility solution. This approach has been conducted through a case study on Greenhouse's PV system in Grenoble, France. We proposed a minimal set of sensors to reduce system complexity while giving us enough information to make decisions. Some technical issues were analyzed as accuracy, sampling rate, response-ability of our system. The influences of inverter operation mode to system losses were considered. After that, we figured out energy problematics in our system based on available design data and simulation data from PVSyst. A PV production prediction model was investigated with input as forecast cloudiness data collected from web service, updated every 3 hours. This model, combined with real-time monitoring data and setting mode on an off-grid inverter, was used to identify control strategies with objectives of avoiding oversize storage capacity and maximizing the autonomous duration of the PV system.